Update of the Portuguese Familial Hypercholesterolaemia Study - Medeiros, A.M. (2011)
The main aim of the Portuguese Familial Hypercholesterolaemia Study is to identify the genetic cause of hypercholesterolaemia in individuals with a clinical diagnosis of Familial Hypercholesterolaemia (FH). A total of 1340 blood samples were collected from 482 index patients and 858 relatives with the collaboration of clinicians from several hospitals all over the country. The genetic diagnosis of FH in this study is based on the analyses of three genes: LDLR, APOB and PCSK9. In the last 10 years, the Portuguese FH Study identified a genetic defect in a total of 171 index patients, corresponding to an overall of 48% of the total received cases with clinical diagnosis of FH. Although the Simon Broome FH register criteria have been adapted to our study, 59 patients that did not fulfil all criteria were included in the study and a mutation causing disease was identified in 8 of these patients. In the LDLR gene were found 80 different mutations in 165 unrelated index patients: 159 heterozygous, 3 compounds heterozygous and 3 true homozygous. The APOB p.Arg3527Gln and the PCSK9 p.Asp374His mutation were not found in any of our patients since our last report, but a novel mutation in the APOB gene, predicted to cause a single amino acid substitution p.Tyr3560Cys, was found in one patient. The cascade screening in relatives of these 171 index patients allowed the identification and genetic characterization of a total of 404 FH patients in Portugal.